Aplikasi Pita Kupu-Kupu pada Busana Exotic Dramatic Style - Dina Gusmita; Mega Kencana; Desi Trisnawati; Fendi Nofrian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The creation of this fashion collection was inspired by the artist's fascination with the butterfly bow a decorative element that offers aesthetic value and enhances the garment's design character. Beyond mere ornamentation, the bow shapes the silhouette, directs visual focus, and lends a feminine, artistic quality to the attire. The work embodies an "exotic dramatic" style, projecting a look that is theatrical, bold, unique, and exotic through the manipulation of silhouettes, details, colors, and materials. Butterfly bow motifs are incorporated into the neckline, bodice, and sleeves of the garments. An exotic flair is achieved by combining Songket Pandai Sikek a traditional woven textile with tulle lace, bridal fabric, organza, and velvet. A color palette of black, maroon, and gold reinforces the "exotic dramatic" aesthetic. Additionally, sequin embellishments serve as decorative elements that further elevate the garment's artistic and aesthetic appeal. The creative process encompassed idea exploration, design planning, material selection, fabrication, and final finishing. The project resulted in three visually striking and innovative ensembles that successfully integrate traditional elements into modern fashion design.